MOTIVASI SISWA SLTP MENGIKUTI BIMBINGAN BELAJAR DI QUANTUM INOVATIF PEKANBARU - Mutia Dewi; Achmad Hidir (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
Special education school or educational tutoring is conducted outside of school either in institutions or not. The cooperation between formal and non-formal education will be maximized in achieving national education goals.But not a few students who rely more on tutoring as non-formal education in achieving learning goals, this happens because the excess kelebiahn-tutoring is not owned by the school. Therefore, the formulation of the problem in this study Adala: 1. What is the motivation to follow the guidance of junior high school students studying in Quantum Innovative Pekanbaru. 2. How junior high student achievement before and after participating in Quantum Innovative tutoring Pekanbaru. Informants or subjects in this study were junior high school students who have studied two semesters following the guidance in Quantum Innovative Pekanbaru, as many as five people.The method in this study is using qualitative. The results of this study were motivated to join junior high school students in tutoring is intrinsic motivation covering want to add insight, and because it is less familiar with the material presented in school teachers. Extrinsic motivation students joined Quantum Innovative include having participated by friends, who close the distance Bimbel and parents on the basis of orders. Student achievement before joining Innovative Quantum is not good and after joining an Innovative Quantum Pekanbaru become better student achievementKeywords: Motivation, Achievement, Tutoring.